التطور الدلالي للكلمة وعلاقتها بسياقات الموقف في شعر مظفر النواب " دراسة دلالية " - كنزة، بالطاهر, نسرين، العلمي; وردة، بن ناجي (Univesity of El-Oued, 2022)
علم الدلالة علم حديث بأصول قديمة، ويعود الفضل فيه لعالم اللغة الفرنسي ميشال بريال (1883م) في بلورة صورته، وعليه أصبح علماً قائماً بذاته، يسعى بحد كبيرإلى دراسة المعنى في نظام اللغة. كون أنَّاللغة ظاهرة اجتماعية تتأثر بقوانين المجتمع، فهي بذلك معرضة للتغير والتطور، ويتضح جليا هذا التطور في المستوى الدلالي لما تقف عليه مظاهر التطور الدلالي من تغيرات بإدخال دلالات جديدة للكلمات، ويلعب السياق دورا ً فعالاً في تحديد هذه الدلالات، فمسألة التطور الدلالي من بين أهم المباحث التي عني بها الباحثين اللغويين و الشعراء، من ذلك الشاعر السياسي الهجائي (مظفر النواب) بتوظيفه صور ومشاهد بفنية محكمة، وتجسيدها على الواقع المعاش عبر انزياحات متعددة أوردها في سياقات مختلفة نفسية اجتماعية، مذهبية سياسية زادت في النص الشعري جمالًا، وجعلت لقصائده أفقًا جديدًا. لقد تم هذا العمل في فصلين، الفصل الأول: وقفنا فيه على أهم المجالات التي يندرج في إطارها البحث الدلالي، ودور السياق في تحديد هذه الدلالة. أما الفصل الثاني: رصد مظاهر التطور الدلالي في شعر مظفر النواب. وختمنا بحثنا بخاتمة تم فيها عرض ورصد بعض النتائج كحوصلة للموضوع Semantics is a modern science with ancient origins, thanks to the French linguist Michel Brial (1883 AD) for crystallizing its image, and accordingly it became a stand-alone science that seeks to a large extent to study the meaning of the language system. The fact that language has a social phenomenon that is affected by the laws of society, so it is subject to change and development, and this development is clearly evident in the semantic level as the manifestations of semantic development stand by changes by introducing new connotations to words, and the context plays an active role in determining these connotations, the issue of semantic development is among the The most important investigations dealt with by linguistic researchers and poets, including the satirical political poet (Muzaffar al-Nawab) by employing images and scenes in a precise technique, and embodying them on the lived reality through multiple deviations that he mentioned in different psychological, social, and political contexts that increased the poetic text beauty, and made his poems a horizon new. This work was carried out in two chapters, the first chapter: we discussed the most important areas in which semantic research falls, and the role of context in determining this significance. The second chapter: Monitoring the manifestations of semantic development in the poetry of Muzaffar al-Nawab. We concluded our research with a conclusion in which some results were presented and monitored as a summary of the topic.
Keywords: التطور الدلالي ,سياق الموقف , شعر; les cheveuxdeveloppement. semantikue